Giving everything for athletic success! - Sports-specific risk acceptance of elite adolescent athletes - Schnell, A.; Mayer, J.; Diehl, K.; Zipfel, S.; Thiel, A. (Psychology of Sport and Exercise, 2014)
Objectives: Good health is the basic foundation for peak performance in elite sports, yet athletes are often conflicted between protecting their health for the sake of being able to compete and risking their health in the form of potential injuries to achieve even higher levels of performance. Adolescent athletes, who are in a sensitive phase of development, are especially prone to negative consequences like injuries or illnesses due to risky behaviors. In an effort to prevent lasting damage, the present study aims to identify groups of athletes who are particularly willing to take risks and the possible determinants of athletes' risk acceptance. Design and method: In our German Young Olympic Athletes' Lifestyle and Health Management (GOAL) Study, we examined 1138 German national squad members, aged 14-18, representing all Olympic sports. Classification tree analyses enabled us to detect determinants of high and low risk groups concerning sports-specific psychosocial and physical risk acceptance. Results: We found several high risk groups. In general, the degree of inclusion in the elite sports system correlates positively with risk acceptance. Athletes who are extremely willing to take physical risks attached high importance to their sports environment and minor importance to their non-sports environment (n = 94; 8%). Athletes who are perfectionists and very focused on their performance were particularly willing to accept physical (n = 142; 13%) and social risks (n = 75; 7%). Conclusion: By identifying extreme groups with an especially high or low willingness to take risks and the determinants of these groups, we can give a more precise picture of elite adolescent athletes' risk acceptance.